2020
DOI: 10.1111/jocs.14492
|View full text |Cite
|
Sign up to set email alerts
|

The impact of intravenous opioid shortages on postoperative pain control in a pediatric cardiac intensive care unit

Abstract: Background The national supply of intravenous pain medications has been restricted since 2018 due to shortages. In late 2017, the ongoing shortages combined with the increased demand for alternative formulations resulted in interruptions in the supply of medications. The cascading effect of interruptions in supply caused hospitals to implement restrictive measures to extend the availability of these medications. This study aims to evaluate differences in pain control in postoperative cardiac patients due to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 6 publications
0
11
0
Order By: Relevance
“…A more recent study reported the opioid requirements of postoperative pediatric cardiac surgical patients for two consecutive years. e average IV morphine equivalents on POD1 were 2.2/2.17 mg/kg/day (2017/2018), and the average for the first five postoperative days was 0.86/0.62 mg/kg/day (2017/ 2018) [14].…”
Section: Discussionmentioning
confidence: 97%
“…A more recent study reported the opioid requirements of postoperative pediatric cardiac surgical patients for two consecutive years. e average IV morphine equivalents on POD1 were 2.2/2.17 mg/kg/day (2017/2018), and the average for the first five postoperative days was 0.86/0.62 mg/kg/day (2017/ 2018) [14].…”
Section: Discussionmentioning
confidence: 97%
“…According to Barnes et al, 2020, fentanyl and hydromorphone were the primary intravenous opioids utilized in response to the limited availability of morphine during the 2018 shortages. An increased use of adjuvant pain medications, including acetaminophen and nonsteroidal antiinflammatory drugs was also seen, but not significantly (Barnes et al, 2020).…”
Section: Therapeutic Alternativesmentioning
confidence: 99%
“…In the study by Barnes et al, 2020, the Children's National Medical Center implemented an opioid stewardship program to address opioid shortages in late 2017. To achieve this, a task force was created to integrate opioid intravenous to per os conversion alerts into daily workflow, educate providers, and send weekly shortage emails.…”
Section: Guidelines and Policiesmentioning
confidence: 99%
See 1 more Smart Citation
“…11 Other subsequent commentaries and studies have confirmed the challenges associated with treating inpatients' pain due to the APQ reductions, [12][13][14][15][16][17][18] including those addressing treating children perioperatively and postoperatively. 19,20 Up to this point, reports of APQ reduction-related shortages of oral opioids are only anecdotal, with numerous reports from patients on social media. In these cases, the patients (generally suffering from chronic non-cancer pain) report that their pharmacies have "run out" of medications that they have taken for many years, although these patients have not been privy to whether these lacks of availability are due to APQ reductions or other supplyside issues within their own pharmacies.…”
mentioning
confidence: 99%